Preparation method and application of hydrophobic confined microbeads based on Ni-based bimetallic biochar
By using scented snowballs to enrich metal ions, Ni-based bimetallic biochar was prepared, and combined with hydrophobic domain-limited bead reactor technology, the problem of poor residual removal of tetracycline antibiotics in water was solved, and efficient and stable catalytic degradation effect was achieved.
Patent Information
- Application Number
- CN202310320607.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-03-29
AI Technical Summary
The prior art is not effective in removing tetracycline antibiotic residues in water, and traditional advanced oxidation methods have problems of metal loss and short ROS life.
The Ni-based bimetallic biochar was prepared by using the scented snowball as the source of biomass carbon, and the porosity was increased by the molten salt-assisted carbonization method. At the same time, the hydrophilic and hydrophobic polymer mixing is used to encapsulate the catalyst to form a hydrophobic confined microbead reactor, effectively limiting ROS and antibiotics to the hydrophilic region for rapid mass transfer and degradation.
It has achieved efficient removal of tetracycline antibiotic residues in water, avoided metal loss, improved the utilization efficiency of ROS, and significantly improved the catalytic degradation effect.
Smart Images

Figure CN116510733B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of material preparation and environmental pollution control, and relates to a preparation method and application of Ni-based bimetallic biochar hydrophobic confined microbeads for efficiently degrading pollutants in wastewater and repairing heavy metals. Background Art
[0002] The rapid growth of social economy has brought about the vigorous development of industry and agriculture, but also caused serious water pollution problems. Among them, tetracycline antibiotics are widely used due to their strong antibacterial ability and low price. They have become the focus of treatment of antibiotic residue pollution in the water environment. In addition, tetracycline antibiotics have a strong enrichment ability and will accumulate in the human body through the food chain, causing allergic reactions. In severe cases, they will have carcinogenic, teratogenic, and mutagenic effects, interfering with various human physiological functions. Therefore, it is of great significance to efficiently remove tetracycline antibiotic residues in water.
[0003] At present, the traditional biological method has a poor effect on the removal of antibiotics. However, the Fenton-like advanced oxidation process can activate hydrogen peroxide (H2O2) or permonosulfate (PMS) through a variety of transition metal-based catalysts to produce highly oxidative reactive oxygen species (ROS) (such as hydroxyl radicals (·OH), sulfate radicals (SO4 ·¯ ), etc.), have shown high removal potential and application prospects in the degradation of antibiotic pollutants. However, Fenton-like advanced oxidation processes still face some disadvantages: 1. Traditional transition metal oxide Fenton-like materials inevitably have the problem of metal loss, which is easy to cause secondary pollution; 2. The ROS generated by the Fenton-like process has a short life span and limited mass transfer distance, resulting in ineffective self-quenching. Summary of the invention
[0004] In view of the problem 1 of the prior art, the present invention selects sweet alyssum (a herbaceous plant) with metal enrichment characteristics as a biomass carbon source, and fully enriches metal ions by watering with metal solutions from the seedling to the mature stage, and then uses molten salt carbonization to prepare it into Ni-based bimetallic biochar (Ni / Fe-MSBC). This technology allows a large number of active bimetallic sites to be evenly formed on the surface and inside of the biochar, while effectively fixing the metal to prevent loss. The molten salt-assisted carbonization method further increases the porosity and defectivity of the biochar, which can improve the adsorption performance.
[0005] In view of the problem 2 of the prior art, the present invention is inspired by the "repulsion effect" of hydrophobic regions on hydrophilic pollutants and ROS, mixes hydrophilic and hydrophobic polymers, and encapsulates the above catalyst, and finally uses phase inversion technology to obtain a porous microbead reactor (Hydrophobic confined beads reactor, HCBRs) with a hydrophobic confined microenvironment. This method can effectively confine ROS and antibiotics to the hydrophilic region for rapid mass transfer and degradation.
[0006] In summary, the Ni-based bimetallic biochar@hydrophobic confined microbead reactor constructed in the present invention provides a new approach for designing high-performance heterogeneous Fenton systems and reveals the synergistic mechanism of the hydrophobic microenvironment confined degradation process.
[0007] A method for preparing hydrophobic confined microspheres based on Ni-based bimetallic biochar, the specific steps are as follows:
[0008] Step 1: Cultivation of sweet alyssum:
[0009] Select a number of healthy and strong sweet alyssum seedlings and transplant them into the soil, dividing them into several groups;
[0010] Watering with metal solution: First, water the sweet alyssum with a certain concentration of NiCl2 solution every day and let it grow for a certain period of time; then, continue to water the sweet alyssum with a certain concentration of FeCl3 solution every day and let it grow for a certain period of time; finally, harvest the roots, stems or leaves of the sweet alyssum, and after washing and drying, obtain the sweet alyssum carbon source rich in Ni-based bimetallic;
[0011] Step 2: Preparation of Ni-based bimetallic biochar Ni / Fe-MSBC:
[0012] A certain amount of Ni-based bimetallic sweet snowball carbon source and a certain proportion of NaCl / KCl mixed salt or KCl / LiCl mixed salt are taken and ground evenly, the mixture is placed in an alumina crucible, then transferred to a tube furnace, calcined for a certain time at a certain temperature and in a nitrogen atmosphere, taken out after natural cooling, the product is fully washed with hot water to remove the molten salt, and Ni / Fe-MSBC is obtained, and ground into powder for standby use;
[0013] Step 3, preparation of Ni / Fe-MSBC@hydrophobic confined microbead reactor:
[0014] Hydrophilic polymer and hydrophobic polymer were selected as the matrix for encapsulating Ni / Fe-MSBC;
[0015] The hydrophilic polymer and the hydrophobic polymer are dissolved in N-methylpyrrolidone (NMP) in proportion, and a certain amount of Ni / Fe-MSBC is added, followed by mechanical stirring at a certain temperature to obtain a microbead reactor casting liquid. Finally, the microbead reactor casting liquid is dripped into deionized water drop by drop, and the deionized water is replaced several times to ensure that the NMP solvent is completely replaced into the water. A hydrophobic confined photo-Fenton composite microbead reactor is obtained through phase inversion, namely, hydrophobic confined microbead HCBRs based on Ni-based bimetallic biochar.
[0016] In step 1, the concentration of the NiCl2 solution is 0.01-2 g / L, the concentration of the FeCl3 solution is 0.01-2 g / L, the mass ratio of Ni / Fe is 10 / 1-1 / 10, and the growth time of irrigating with Ni ion solution and Fe ion solution is 15-25 days.
[0017] In step 2,
[0018] The mass ratio of the Ni-based bimetallic sweet alyssum carbon source, NaCl and KCl is 0.5 g: 2.96 g: 3.68 g;
[0019] or,
[0020] The mass ratio of the Ni-based bimetallic sweet apricot carbon source, LiCl and KCl is 0.5 g: 2.51 g: 3.04 g;
[0021] The calcination temperature is 500-900 °C, the calcination time is 3-5 h, and the heating rate of the tube furnace is 5 °C / min;
[0022] In step 3,
[0023] The hydrophilic polymer is polyacrylonitrile PAN, cellulose acetate CA or polysulfone PSF.
[0024] The hydrophobic polymer is polyvinylidene fluoride (PVDF), polydimethylsiloxane (PDMS) or polytetrafluoroethylene (PTFE).
[0025] In step 3, the mass percentage of the Ni / Fe-MSBC powder, NMP, hydrophilic polymer and hydrophobic polymer is 2.5 wt %:87.5 wt %:0~10 wt %:10~0 wt %, the mechanical stirring temperature is 50-70 °C, and the stirring time is 4-6 h. The NMP described in the above technical solution acts as a solvent to dissolve PAN and PVDF to prepare a microbead reactor.
[0026] The PAN / PVDF described in the above technical solution acts as a matrix and simultaneously adjusts the hydrophilic and hydrophobic environment.
[0027] The Ni-based bimetallic biochar-based hydrophobic confined microbeads HCBRs prepared by the present invention are used for photo-Fenton degradation of tetracycline antibiotics.
[0028] Evaluation of photocatalytic activity: First, add 50 mL of tetracycline solution to a 100 mL double-layer beaker, then add microbeads (1.0 g) and magnets, turn on the circulating water, and stir with a magnetic stirrer for 60 min. Then, add a certain amount of H2O2 and H2SO4 to the above solution (adjust the pH from 1.7 to 7.0), turn on the xenon lamp to start the reaction. At a certain time interval, extract 3.0 mL of the solution, filter it through a syringe (0.22 μm), and quickly detect it with a UV spectrophotometer.
[0029] The beneficial effects of the present invention are:
[0030] (1) The biochar prepared by calcining with molten salt using metal-irrigated sweet alyssum as raw material has metal in-situ enrichment in its internal and surface structures and has dual or even multi-sites, thereby generating more free radicals and greatly improving the catalytic efficiency. The prepared biochar can also effectively fix metals to prevent their loss, achieving a sustained and stable catalytic degradation effect, thereby effectively repairing heavy metals and degrading organic pollutants.
[0031] (2) The photo-Fenton catalyst was fixed in the microbead reactor prepared by blending hydrophilic PAN and hydrophobic PVDF, forming a hydrophobic confined microenvironment, which effectively solved the problem of insufficient ROS utilization. The entire preparation method is simple and convenient, with strong universality, and provides new insights for the optimization and application of Fenton-like catalytic systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 TEM image of HCBRs prepared in Example 1;
[0033] Figure 2 HR-TEM image of HCBRs prepared in Example 1;
[0034] Figure 3 The SEM image of HCBRs prepared in Example 1; the inset is an image of an actual sample of HCBRs;
[0035] Figure 4 The water contact angle data of HCBRs prepared with different ratios of PAN and PVDF;
[0036] Figure 5 The degradation diagram of antibiotics by HCBRs made of different ratios of PAN and PVDF;
[0037] Figure 6 Figure 2 is the relationship between HCBRs prepared with different ratios of PAN and PVDF and the degradation kinetic constants. DETAILED DESCRIPTION
[0038] The present invention will be further described below with reference to the accompanying drawings and specific implementation examples.
[0039] The present invention takes the total mass of the casting liquid of the microbead reactor as 20 g as an example.
[0040] Example 1
[0041] (1) Cultivation of sweet alyssum
[0042] The sweet alyssum was irrigated with a NiCl2 solution with a concentration of 0.8 g / L every day and grown for 15 days, and then the sweet alyssum was irrigated with a FeCl3 solution with a concentration of 0.8 g / L every day and grown for 15 days; finally, the roots, stems or leaves of the sweet alyssum were harvested, and after washing and drying, a sweet alyssum carbon source rich in Ni-based bimetallic was obtained;
[0043] (2) Preparation of Ni-based bimetallic biochar (Ni / Fe-MSBC)
[0044] 0.5 g of Ni-rich bimetallic sweet alyssum root, 2.96 g of NaCl and 3.68 g of KCl were ground and mixed evenly in a crucible, transferred to a tube furnace, calcined at 800 °C for 3 h at a heating rate of 5 °C / min, and taken out after natural cooling to obtain Ni / Fe-MSBC for standby use;
[0045] (3) Preparation of Ni / Fe-MSBC@HCBRs
[0046] Firstly, 1.2 g PVDF powder, 0.8 g PAN powder, 0.05 g Ni / Fe-MSBC and 17.95 g NMP solvent were weighed and mixed, and the microbead reactor casting liquid was obtained after heating and stirring. Then, 20 g of the microbead reactor casting liquid was weighed, drawn into a 10 mL syringe, and dripped into deionized water drop by drop. After phase inversion, the composite microbead reactor HCBRs was obtained.
[0047] Figure 1 This is the TEM image of HCBRs prepared in Example 1; it can be seen that Ni and Fe are evenly distributed on the biochar sheet; Figure 2 HR-TEM image of HCBRs prepared in Example 1; lattice spacing is 0.248 nm;
[0048] Figure 3This is the SEM image of HCBRs prepared in Example 1; the inset is the actual sample image of HCBRs; the surface of HCBRs is rough, showing obvious porosity, and its volume is small, which is easy to quantify and store.
[0049] Example 2
[0050] Under the condition that other conditions remain unchanged, a group experiment was conducted to optimize Ni / Fe-MSBC, and a comparative experiment was established as follows: the sweet alyssum seedlings were divided into 7 groups.
[0051] Group A was irrigated with only 0.8 g / L NiCl2 solution.
[0052] Group B was irrigated with only 0.8 g / L FeCl3 solution.
[0053] Group C was irrigated with 0.01 g / L NiCl2 solution and 0.8 g / L FeCl3 solution.
[0054] Group D was irrigated with 2 g / L NiCl2 solution and 0.8 g / L FeCl3 solution;
[0055] Group E was irrigated with 0.8 g / L NiCl2 solution and 0.01 g / L FeCl3 solution.
[0056] Group F was irrigated with 0.8 g / L NiCl2 solution and 2 g / L FeCl3 solution;
[0057] By changing the concentrations of Ni and Fe ions, the effects of both concentrations on the removal rate of tetracycline in water were explored. The best effect was achieved when the ion concentration was 0.8 g / L. The dual metal effect was better than that of a single metal.
[0058] Table 1 Effect of different Ni ion and Fe ion concentrations on removal rate
[0059]
[0060] Example 3
[0061] While ensuring that other conditions remain unchanged, the ratio of PVDF and PAN is adjusted to construct control groups 1 to 8, and the degradation rate of the product on tetracycline is examined. The comparative test is established as follows:
[0062] 2 g of the blend of PVDF and PAN, 0.2 g of Ni / Fe-MSBC were weighed, mixed with 17.8 g of NMP solvent, heated and stirred, and then hydrophilic HCBR-PAN and hydrophobic HCBR-PVDF were obtained by phase inversion, so as to explore the performance of degrading wastewater after mixing only PVDF or PAN powder with the catalyst. The results showed that the HCBRs constructed in Example 1 had the best performance;
[0063] Table 2 Effect of different ratios of PVDF and PAN on degradation rate
[0064]
[0065] Figure 4 The water contact angle data of HCBRs prepared in Example 1 with different ratios of PAN and PVDF is shown in FIG. In the blend of PAN and PVDF, the amount of PAN is gradually increased, and the amount of PVDF is correspondingly reduced, and the contact angle shows a downward trend;
[0066] Figure 5 The figure is the degradation diagram of antibiotics by HCBRs made of PAN and PVDF in different proportions; the surface of hydrophilic microbeads easily adsorbs water-soluble pollutants and H2O2, and forms free radicals under light to achieve a good degradation effect. However, the present invention finds that the effect is not the best when the water contact angle is the smallest. In the blend of PAN and PVDF, when the ratio of PAN:PVDF is 0:10, 2:8, 3:7, and 4:6, the degradation rate is increasing, but when the ratio of PAN:PVDF is 5:5, 6:4, 7:3, and 8:2, the degradation rate gradually decreases. It can be seen that when the mass percentage of PAN / PVDF reaches 4:6, the degradation performance of antibiotics is the best, reflecting the advantages of the hydrophobic confined microenvironment: the hydrophilic and hydrophobic polymers are evenly mixed, and after the bead reactor is transformed into a phase-transformed bead reactor, a microenvironment between hydrophilic / hydrophobic phases is formed at the microscopic level, wherein the hydrophobic microenvironment limits the diffusion of hydrophilic reactants (ROS and pollutants, etc.) and concentrates them in the hydrophilic area, thereby accelerating the reaction mass transfer efficiency and improving the degradation performance.
[0067] Figure 6 The relationship between HCBRs prepared with different ratios of PAN and PVDF and the degradation kinetic constants. Figure 6 It can be seen that when the mass ratio of PVDF and PAN is 6:4, the tetracycline degradation kinetic constant of the finally constructed HCBRs increases significantly, which is about 4.4 times and 1.5 times higher than that of single hydrophobic and hydrophilic reactors, respectively.
[0068] In summary, the preparation method of the Ni-based bimetallic biochar@hydrophobic confined microbead reactor of the present invention has the advantages of simple process, convenient operation, wide source of raw materials, low cost, mild reaction conditions, and green environmental protection. The prepared Ni-based bimetallic biochar@hydrophobic confined microbead reactor has the advantages of stable structure and strong catalytic activity. It can catalytically degrade organic pollutants such as antibiotics in water bodies with high removal efficiency and no secondary pollution. It has high use value in the treatment of polluted water bodies and has broad application prospects.
[0069] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A method for preparing hydrophobic confined microbeads based on Ni-based bimetallic biochar, characterized in that: The specific steps are as follows: Step 1: Cultivation of sweet alyssum: Select a number of healthy and strong sweet alyssum seedlings and transplant them into the soil, dividing them into several groups; Watering with metal solution: First, water the sweet alyssum with a certain concentration of NiCl2 solution every day and let it grow for a certain period of time; then, continue to water the sweet alyssum with a certain concentration of FeCl3 solution every day and let it grow for a certain period of time; finally, harvest the roots, stems or leaves of the sweet alyssum, and after washing and drying, obtain the sweet alyssum carbon source rich in Ni-based bimetallic; Step 2: Preparation of Ni-based bimetallic biochar Ni / Fe-MSBC: A certain amount of Ni-based bimetallic sweet snowball carbon source and a certain proportion of NaCl / KCl mixed salt or KCl / LiCl mixed salt are taken and ground evenly, the mixture is placed in an alumina crucible, then transferred to a tube furnace, calcined for a certain time at a certain temperature and in a nitrogen atmosphere, taken out after natural cooling, the product is fully washed with hot water to remove the molten salt, and Ni / Fe-MSBC is obtained, and ground into powder for standby use; The mass ratio of the Ni-based bimetallic aromatic charcoal source, NaCl and KCl is 0.5 g: 2.96 g: 3.68 g; or, the mass ratio of the Ni-based bimetallic aromatic charcoal source, LiCl and KCl is 0.5 g: 2.51 g: 3.04 g; Step 3, preparation of Ni / Fe-MSBC@hydrophobic confined microbead reactor: Hydrophilic polymer and hydrophobic polymer were selected as the matrix for encapsulating Ni / Fe-MSBC; The hydrophilic polymer and the hydrophobic polymer are dissolved in N-methylpyrrolidone in proportion, and then a certain amount of Ni / Fe-MSBC is added, followed by mechanical stirring at a certain temperature to obtain a microbead reactor casting liquid, and finally the microbead reactor casting liquid is dripped into deionized water drop by drop, and the deionized water is replaced several times to ensure that the N-methylpyrrolidone solvent is completely replaced into the water, and a hydrophobic confined photo-Fenton composite microbead reactor is obtained through phase inversion, that is, a hydrophobic confined microbead HCBRs based on Ni-based bimetallic biochar; The mass percentage of the Ni / Fe-MSBC powder, N-methylpyrrolidone, hydrophilic polymer and hydrophobic polymer is 0.25 wt %:89.75 wt %:4 wt %:6 wt % or 1 wt %:89 wt %:2-8 wt %:8-2 wt %; The hydrophilic polymer is polyacrylonitrile, cellulose acetate or polysulfone; The hydrophobic polymer is polyvinylidene fluoride, polydimethylsiloxane or polytetrafluoroethylene.
2. The preparation method according to claim 1, characterized in that: In step 1, the concentration of the NiCl2 solution is 0.01-2 g / L, the concentration of the FeCl3 solution is 0.01-2 g / L, the mass ratio of Ni / Fe is 10 / 1-1 / 10, and the growth time of irrigating with Ni ion solution and Fe ion solution is 15-25 days.
3. The preparation method according to claim 1, characterized in that: In step 2, the calcination temperature is 500-900°C, the calcination time is 3-5 h, and the heating rate of the tubular furnace is 5°C / min.
4. The preparation method according to claim 1, characterized in that: In step 3, the mechanical stirring temperature is 50-70° C., and the stirring time is 4-6 h.
5. Application of the hydrophobic confined microbeads based on Ni-based bimetallic biochar prepared by the preparation method described in any one of claims 1 to 4 in photo-Fenton degradation of tetracycline antibiotics in wastewater.
Citation Information
Patent Citations
Preparation method and application of biochar by enriching iron element in cattail roots
CN109847750A
Preparation method and application of ferric oxide@biomass carbon fiber@pDA-PVDF (polydiacetylene-polyvinylidene fluoride) light Fenton composite beads
CN109999809A
Method for removing hexavalent chromium in water by using biochar-loaded nanometer iron-nickel composite material
CN110745935A